Channeling of Electron Transport to Improve Collection Efficiency in Mesoporous Titanium Dioxide Dye Sensitized Solar Cell Stacks - Fakharuddin, Azhar; Irfan, Ahmed; Zulkeflee, Kalidin; M. M., Yusoff; Rajan, Jose (AIP Publishing LLC, 2014)
Dye-sensitized solar cell (DSC) modules are generally made by interconnecting large photoelectrode strips with optimized thickness (∼14 μm) and show lower current density (JSC ) compared with their single cells. We found out that the key to achieving higher JSC in large area devices is optimized photoelectrode volume (VD ), viz., thickness and area which facilitate the electron channeling towards working electrode. By imposing constraints on electronic path in a DSC stack, we achieved >50% increased JSC and ∼60% increment in photoelectric conversion efficiency in photoelectrodes of similar VD (∼3.36 × 10−4 cm3) without using any metallic grid or a special interconnections.